2013
DOI: 10.4028/www.scientific.net/amr.734-737.2181
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of the C<sub>2</sub>H<sub>5</sub>COOH-Graphite Intercalation Compound

Abstract: The graphite intercalation compound with easy low temperature exfoliated and high exfoliated volume was prepared by chemical oxidation method using natural graphite flakes, C2H5COOH, FeCl3 and CrO3 as raw materials, according to the mass ratio of 1:2.8:0.3:0.2. The expansion volume of graSubscript textphite intercalation compounds was 320 mL•g-1 at 300°C and achieved biggest 580 mL•g-1 at 700°C. The composition, structure and properties of the graphite intercalation compound were characterized and analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the specific case of graphite, this can result in the formation of graphite intercalation complexes (GICs) [1][2][3][4][5][6][7][8][9][10][11][12][13] and in the case of tetraalkylammonium (R 4 N + ) reduction at graphite cathodes, has been found to be accompanied by a significant irreversible volumetric expansion of the host graphite [14][15][16], irrespective of whether intercalation is electrochemical [17,18] or non-electrochemical [16,19]. Various chemical routes to R 4 N + and alkali metal GIC syntheses have been presented [16,[20][21][22] often taking place via cationic displacement reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of graphite, this can result in the formation of graphite intercalation complexes (GICs) [1][2][3][4][5][6][7][8][9][10][11][12][13] and in the case of tetraalkylammonium (R 4 N + ) reduction at graphite cathodes, has been found to be accompanied by a significant irreversible volumetric expansion of the host graphite [14][15][16], irrespective of whether intercalation is electrochemical [17,18] or non-electrochemical [16,19]. Various chemical routes to R 4 N + and alkali metal GIC syntheses have been presented [16,[20][21][22] often taking place via cationic displacement reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of EG with H 2 SO 4 in the presence of oxidants has been studied most extensively [9][10], and intensive research effort has been concentrated on the sulfur-free EG or GICs. For example, Zhou Mingshan et al [11] prepared GICs used NG, CrO 3 and HClO 4 as raw materials, the maximum EV can achieved 555mL/g in 2011, and then Zhou Ming-shan and Jiancai Xia [12] prepared GICs used NG, C 2 H 5 COOH, FeCl 3 and CrO 3 as raw materials, the maximum EV of up to 580mL/g in 2013; M. V. Savos'kin et al [13] reported the synthesis of expandable graphite in the systerm HNO 3 -CH 3 COOH-H 2 O; Li Jihui et al [14] reported the preparation of low sulfur EG with acetic anhydride as intercalation agent, H 2 O 2 and K 2 Cr 2 O 7 as the oxidant, EV was 280 mL/g; Jijin Zhao et al [15] reported the preparation and microstructure of EG with large expanding volume by two-step intercalation, using HNO 3 and CH 3 COOH as reaction medium, the maximum EV can reach 450mL/g. Based on this background, we aimed to prepared sulfur-free EG in the Graphite-HClO 4 -CH 3 COOH Systerms, and analyzed the influence factors on the EV by single factor experiments and orthogonal experiments.…”
Section: Introductionmentioning
confidence: 99%